The Development of Reading Ability on Words with Non-Corresponding Final Consonants and Listening-Speaking Abilities by Using Brain-Based Learning Integrated with Educational Games for Grade 1 Students - Samakkee, Phattharawadee; Ongrardwanich, Namthip (Journal of Buddhist Education and Research (JBER), 2026)
The purpose of this research was : 1) to develop a learning management plan using Brain-Based Learning integrated with Educational games to enhance reading ability on words with non-corresponding final consonants and listening-speaking abilities for Grade 1 students, 2) to compare the reading ability on words with non-corresponding final consonants for Grade 1 students before and after studying, and 3) to compare listening-speaking abilities for Grade 1 students before and after studying. The sample group in this research consisted of 6 Grade 1 students from Semester 2, Academic Year 2025, at Banyangsai Prommaprachason School, Muang District, Sukhothai Province. They were selected using a cluster sampling method, with the school as the sampling unit. The research instruments included: 1) A learning management plan using Brain-Based Learning integrated with educational games to enhance reading ability on words with non-corresponding final consonants and listening-speaking abilities for Grade 1 students, 2) A test to measure the reading ability on words with non-corresponding final consonants, and 3) A test to measure listening-speaking abilities. Data were analyzed using mean, standard deviation, percentage, and the Wilcoxon Signed Rank Test. The research results indicate that: 1) The development of the learning management plan using Brain-Based Learning integrated with Educational games were the highest (x̄ = 4.52, S.D. = 0.51), 2) The comparison of students’ reading ability on words with non-corresponding final consonants after studying showed a significant improvement compared to before studying at a statistical significance level of .05, and 3) The comparison of students’ listening-speaking abilities after studying showed a significant improvement compared to before studying at a statistical significance level of 0.05.